1976
DOI: 10.1128/iai.13.3.836-843.1976
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effects of leukocidin from Pseudomonas aeruginosa on polymorphonuclear leukocytes from cattle

Abstract: The cytotoxic action of leukocidin from Pseudomonas aeruginosa was studied in vitro by following the release of various intracellular markers from polymorphonuclear leukocytes from cattle (PMLC). Low-molecular markers (K+, 86Rb+, glucose) were lost from PMLC within 1 to 2 min after the addition of leukocytes. The release of high-molecular-weight indicators (51Cr, bound to intracellular protein; lactate dehydrogenase) occurred only after swelling of the cells, leading to an increased permeability of the plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
1
1

Year Published

1982
1982
1986
1986

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 16 publications
2
27
1
1
Order By: Relevance
“…10, electron microscopy indicated an increase of vacuoles in the leukocidin-treated leukocytes. Accordingly, the toxic action of pseudomonal leukocidin may not be explained only by the production of lesions on the cell membrane as postulated by Scharmann (20), but may be related to cellular biochemical processes.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…10, electron microscopy indicated an increase of vacuoles in the leukocidin-treated leukocytes. Accordingly, the toxic action of pseudomonal leukocidin may not be explained only by the production of lesions on the cell membrane as postulated by Scharmann (20), but may be related to cellular biochemical processes.…”
Section: Discussionmentioning
confidence: 97%
“…Preparation if leukocidin. P. aeruginosa 158 used in this study was shown to produce leukocidin by Scharmann (18)(19)(20)(21)(22) and kindly supplied by Lutz, Institute of Pharmacology and Toxicology, Justus-Lieberg-University. The microorganisms were grown on a trypticase soy broth medium containing 0.5% glucose with a reciprocal shaker (120 cycles/min) at 30 C for 12 hr.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the anaerobes, an extracellular cytotoxin with a n apparent MW of 3,500 has been obtained from Bacteroides gingivalis and B. asaccharolyticus but not B. melaninogenicus (van Steenbergen et a / 1982). Leucocidins assayed on bovine PBL include those produced by Pseudomonas aeruginosa (Scharmann 1976) and Pasfeureffa haemofytica (Baluyut et a/ 1981). The latter possesses biochemical and physical properties virtually identical to those described for F.necrophorum in the present study, in that it is a heat-labile protein, has a M W around 300,000, is inactivated by extremes of p H , especially acid p H , and is produced by P.haemo/ytica during logarithmic growth (Baluyut e t a / 1981).…”
mentioning
confidence: 99%
“…No enzymatic activities are known for this protein and it probably acts primarily on the target cell membrane n u t z et Lutz, 1979). One of the first measurable effects of this toxin in the dose range of 1-50 pg/ml is a rapid increase in cell membrane permeability for ions and small molecules such as potassium, sodium, and glucose, but not for large molecules (Lutz et al, 1982;Maurer and Lutz, 1984;Scharmann, 1976). Therefore cytotoxin appears to create a n initially discrete transmembrane lesion.…”
mentioning
confidence: 99%